HUDUD PUNISHMENTS IN ISLAMIC CRIMINAL LAW - Okon, Etim E. (European Scientific Journal, ESJ, 2014)
Islam is more than a religion, it encompasses faith, culture, law and the social order. Islam proposes a society of righteousness and justice. Criminal behaviour is not tolerated in the Islamic order of society. Criminal behaviour is breach of God’s sovereignty, hence stiffer penalties are prescribed. This paper examines hudud punishments in Islamic penal system, and agitates for the reformation of Islamic criminal jurisprudence. While it is reasonable to punish offenders, and violators of normative principles, it is the opinion of this paper that punishments that are prescribed in municipal penal code should at least conform to international criminal jurisprudence.